RGDV-modified gemcitabine: a nano-medicine capable of prolonging half-life, overcoming resistance and eliminating bone marrow toxicity of gemcitabine - Liu W (Dove Medical Press, 2019)
Wenchao Liu1,2, Yujia Mao1,2, Xiaoyi Zhang1,2, Yaonan Wang1,2, Jianhui Wu1,2, Shurui Zhao1,2, Shiqi Peng1,2, Ming Zhao1–3 1Beijing Area Major Laboratory of Peptide and Small Molecular Drugs, Department of Medicinal Chemistry, School of Pharmaceutical Sciences, Capital Medical University, Beijing 100069, People’s Republic of China; 2Engineering Research Center of Endogenous Prophylactic of Ministry of Education of China, Department of Medicinal Chemistry, School of Pharmaceutical Sciences, Capital Medical University, Beijing 100069, People’s Republic of China; 3Department of Biomaterials, Beijing Laboratory of Biomedical Materials and Key Laboratory of Biomedical Materials of Natural Macromolecules, Beijing University of Chemical Technology, Beijing 100026, People’s Republic of ChinaCorrespondence: Ming ZhaoBeijing Area Major Laboratory of Peptide and Small Molecular Drugs, Department of Medicinal Chemistry, School of Pharmaceutical Sciences, Capital Medical University, No. 10, Youanmenwaixitoutiao, Fengtai District, Beijing 100069, People’s Republic of ChinaTel +86 108 391 1535Email mingzhao@bjmu.edu.cnBackground: Gemcitabine has been widely used as a chemotherapeutic drug. However, drug resistance, short half-life and side effects seriously decrease its chemotherapeutic efficacy.Purpose: The object of preparing RGDV-gemcitabine was to prolong the half-life, to overcome drug resistance and to eliminate bone marrow toxicity of gemcitabine.Methods: Arg-Gly-Asp-Val was coupled with gemcitabine, forming 4-(Arg-Gly-Asp-Val-amino)-1-[3,3-difluoro-4-hydroxy-5-(hydroxylmethyl)oxo-lan-2-yl]pyrimidin-2-one (RGDV-gemcitabine) involving 9-step reactions. The advantages of RGDV-gemcitabine to gemcitabine were demonstrated by a series of assays, such as in vitro half-life assay, in vitro drug resistance assay, in vivo anti-tumor assay, in vivo kidney toxicity assay, in vivo liver toxicity assay and in vivo marrow toxicity assay. The nano-features of RGDV-gemcitabine were visualized by TEM, SEM and AFM images. The tumor-targeting action and release of RGDV-gemcitabine were evidenced by FT-MS spectra.Results: Half-life and anti-tumor activity of RGDV-gemcitabine were 17-fold longer and 10-fold higher than that of gemcitabine, respectively. RGDV-gemcitabine, but not gemcitabine, showed no kidney toxicity, no liver toxicity, no marrow toxicity and no drug resistance. The advantages attributed to the nanofeatures of RGDV-gemcitabine were targeting tumor tissue and releasing gemcitabine in tumor tissue.Conclusion: RGDV-gemcitabine successively overcame the defects of gemcitabine and provided a practical strategy of nano-medicine.Keywords: gemcitabine, modification, half-life, anti-tumor, tumor targeting, release, toxicity, nano-species